Highly robust interfacially polymerized PA layer on thermally responsive semi-IPN hydrogel: toward on-demand tuning of porosity and surface charge - Gupta, Nupur (2022)
Hydrogel composites with skin layer that allows fast and selective rejection of molecules possess high potential for numerous applications, including sample preconcentration for point-of-use detection and analysis. The stimuli-responsive hydrogels are particularly promising due to facile regenerability. However, poor adhesion of the skin layer due to swelling-degree difference during continuous swelling/deswelling of the hydrogel hinders its further development. In this work, a polyamide skin layer with strong adhesion was fabricated via gel-liquid interfacial polymerization (GLIP) of branched polyethyleneimine (PEI) with trimesoyl chloride (TMC) on a cross-linked N-isopropyl acrylamide hydrogel network containing dispersed poly sodium acrylate (PSA), while the traditional m-phenylenediamine (MPD)-TMC polyamide layer readily delaminates. We investigated the mechanistic design principle, which not only resulted in strong anchoring of the polyamide layer to the hydrogel surface but also enabled manipulation of the surface morphology, porosity, and surface charge by tailoring interfacial reaction conditions. The polyamide/hydrogel composite was able to withstand 100 cycles of swelling/deswelling without any delamination or a significant decrease in its rejection performance of the model dye, i.e., methylene blue. Regeneration can be done by deswelling the swollen beads at 60 °C, which also releases any loosely bound molecules together with absorbed water. This work provides insights into the development of a physically and chemically robust skin layer on various types of hydrogels for applications such as preconcentration, antifouling-coating, selective compound extraction, etc.